2004
DOI: 10.1074/jbc.m400415200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of ZFP-57, a Novel Zinc Finger Transcription Factor in the Mammalian Peripheral Nervous System

Abstract: To isolate new zinc finger genes expressed at early stages of peripheral nerve development, we have used PCR to amplify conserved zinc finger sequences. RNA from rat embryonic day 12 and 13 sciatic nerves, a stage when nerves contain Schwann cell precursors, was used to identify several genes not previously described in Schwann cells. One of them, zinc finger protein (ZFP)-57, proved to be the homologue of a mouse gene found in F9 teratocarcinoma cells. Its mRNA expression profile within embryonic and adult no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…(B) Nmnat1/EGFP is homogeneously distributed, apart from exclusion from nucleoli. N70/EGFP (C) and EGFP (D) alone are homogeneously distributed throughout the cell but EGFP has a preference for the nucleus as previously described (Alonso et al, 2004). Neither is targeted to intranuclear foci.…”
Section: Discussionmentioning
confidence: 76%
“…(B) Nmnat1/EGFP is homogeneously distributed, apart from exclusion from nucleoli. N70/EGFP (C) and EGFP (D) alone are homogeneously distributed throughout the cell but EGFP has a preference for the nucleus as previously described (Alonso et al, 2004). Neither is targeted to intranuclear foci.…”
Section: Discussionmentioning
confidence: 76%
“…30 In adult mouse organs, Zfp57 is highly expressed in testis and brain. 31,32 Loss of the zygotic function 13 of Zfp57 causes partial lethality, while eliminating both the maternal and zygotic functions of Zfp57 leads to complete embryonic lethality. 26 Several reports have suggested that this transcription factor binds to KRAB-associated protein 1 (KAP1), a scaffold protein for various heterochromatin-inducing factors, through its KRAB domain, and is involved in genome imprinting by recruiting KAP1 to several ICRs.…”
Section: Discussionmentioning
confidence: 99%
“…KRAB-ZNF proteins comprise the largest protein family of transcriptional corepressors with more than 290 KRAB-ZNF coding genes found in the human genome [17]. KRAB-ZNF proteins regulate differential gene expression during embryonic development, organogenesis, cell differentiation, proliferation and apoptosis [17][18][19]. KRAB-ZNF factors show a highly conserved domain structure and harbour a variable number of ZNF motifs, which regulate their sequence specific DNA binding to regulatory regions of their target genes [17].…”
Section: Introductionmentioning
confidence: 99%